A note on units in $\mathbb{F}_q SL(2, \mathbb{Z}_3)$ - Maheshwari , S.; Sharma , R. K. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 512.5Let $R$ be a ring, and $ SL(2,R)$ be the special linear group of $2×2$ matrices with determinant $1$ over $R$. We obtain the Wedderburn decomposition of$\dfrac{\mathbb{F}_q SL(2,\mathbb{Z}_3)}{J(\mathbb{F}_q SL(2,\mathbb{Z}_3))}$ and show that $ 1+J(\mathbb{F}_q SL(2,\mathbb{Z}_3))$ is a non-Abelian group, where $\mathbb{F}_q$ is a finite field with $q = p^k$ elements of characteristic $2$ and $3.$